Family Planning Decision in the Context of Women Empowerment: Case of a Middle-income Economy - Urooj, Komal; Ahmad, Tusawar Iftikhar; Nawaz, Muhammad Atif; Bhatti, Muhammad Azhar (iRASD Journal of Economics, 2023)
Family planning is essential for sustainable development, particularly for a lower middle income country like Pakistan, the fifth most densely inhabited country in the world. Women's empowerment leads to a dynamic role in family planning decisions. Based on the data of PDHS 2017-18 and by taking a sample of 12339 married women, this study aims to explore the connection between women empowerment and family planning decisions in Pakistan. A summative women empowerment index was calculated for the five dimensions (economic empowerment, financial inclusion, participation in decision making, self-esteem, and awareness status). Findings of binary logistics showed that women's empowerment (as an index) has a positive effect on the use of contraceptives. Every dimension of women's empowerment except her financial inclusion positively affects family planning decisions. Household wealth status increases the probability of using contraceptives. Due to regional disparities, contraceptive usage is shallow in Sindh, Balochistan, AJK, and FATA.